Features of Distribution of the Tularemia Infection in the Rostov Region - E. V. Kovalev; G. V. Karpushchenko; M. M. Schwager; A. V. Polonsky; V. V. Sidelnikov; A. Yu. Goncharov; N. V. Polovinka (Эпидемиология и вакцинопрофилактика)
Since 1933 in the Rostov region, the official registration of tularemia began. In 1964-1949 the highest incidence was noted. Since 1947, they have been vaccinated against tularemia. In 1966 to 1973, there were no cases of tularemia. In July-August 1993, a large outbreak of tularemia (more than 200 people) was recorded. Until early 2017, the epidemic situation in tularemia in the Rostov region, according to the data of long-term monitoring, was assessed as stable, but low coverage with vaccinations against tularemia, both in the population of endemic territories and in individuals of certain professional categories was recorded. In january 2017, two residents of Rostov-on-Don received a clinical diagnosis of «tularemia». In june and july 2017, three cases of tularemia were reported. The most effective mechanism for preventing the spread of tularemia remains vaccination of the population from the contingent of risk. We consider it advisable to conduct studies of the immunity to tularemia in the population vaccinated in the last five years, to significantly increase the reliability of short- and long-term prognosis for tularemia in the region.